RANCANG BANGUN APLIKASI AUTOCARE+ BERBASIS MOBILE SEBAGAI SOLUSI DIGITALISASI MANAJEMEN DAN PEMBAYARAN PADA BENGKEL UMKM - Haikal Buana Maulidina; Muhammad Rabil Wahid; Nur Imam Afriansyah; Mohamad Wilman Saputra; Genta Nazwar Tarempa (Journal of Information System, Applied, Management, Accounting and Research, 2026)
The advancement of digital technology encourages Micro, Small, and Medium Enterprises (MSMEs), particularly in the vehicle repair service sector, to adapt to technology-based systems to improve operational performance. However, in practice, many workshops still run their business processes conventionally, causing various problems such as unorganized data recording, disorganized customer queues, and inaccuracies in cost calculations and financial reports. This study aims to develop the AutoCare+ mobile application equipped with digital payment system (e-wallet) integration to support the digitalization of workshop services. The methods used in this study include the requirements analysis stage using the SWOT approach, user interface design (UI/UX), and the system implementation process. Testing was carried out using the Black Box Testing method to ensure that every function in the application works properly. The results show that the AutoCare+ application is able to present service booking features, transaction history recording, and a digital payment system with a functional success rate of 100%. The application of fintech technology in this application has been proven to improve operational efficiency, provide cost transparency to customers, and reduce the potential for recording errors that often occur in manual systems.